HANDS-ON VISUAL STUDIO 2022 a developer's guide to exploring new features and best practices in VS2022 for maximum productivity - Teheran Garcia, Miguel Angel (PACKT PUBLISHING LIMITED, 2022)
Learn to design, develop, debug, and deploy technologies by harnessing the full power of Visual Studio 2022 by discovering its new features and exclusive techniques Key Features Discover solutions to common problems faced while using Visual Studio 2022 Explore tips, tricks, and best practices and discover ways to overcome source-code challenges Deep dive into Visual Studio's new features and unleash its potential to enhance your coding journey Book Description Visual Studio 2022 is the complete and ideal integrated development environment (IDE) for creating large, complex, and scalable applications. It is one of the most complete tools available for development, especially with Microsoft technologies. This book will teach you how to take advantage of the tools available with this IDE to write clean code faster. You'll begin by learning how to set up and start Visual Studio 2022 and how to use all the tools provided by this IDE. You will then explore key combinations, tips, and additional utilities that can help you to code faster and review your code constantly. Next, you will see how to compile, debug, and inspect your project to analyze its current behavior using Visual Studio. The book also shows you how to insert reusable blocks of code writing simple statements. Later, you will learn about visual aids and artificial intelligence that will help you improve productivity and understand what is going on in the project. By the end of this book, you will be able to set up your development environment using Visual Studio 2022, personalize the tools and layout, and use shortcuts and extensions to improve your productivity. What you will learn Understand what's new in Visual Studio 2022 Discover the various code tools to improve productivity Explore the benefits of using .NET 6 in Visual Studio 2022 Perform compilation, debugging, and version control comfortably Become well-versed with various shortcuts, tricks, tips, and tools to improve productivity within Visual Studio 2022 Implement remote and collaborative work with Visual Studio 2022 Who this book is for This book is for .NET software developers focusing on web development and web developers who want to learn about the new features, tools, and features available in Visual Studio 2022. Basic knowledge of HTML, CSS, and JavaScript or frameworks such as React and Angular is assumed.